2015
DOI: 10.1007/s00198-015-3219-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D, parathyroid hormone, calcium intake, and bone mineral density in Spanish adults

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 Mini AbstractVitamin D insufficiency was very common among Spanish community-dwelling adult subjects. A threshold of serum 25(OH)D around 30 ng/ml would be necessary for the prevention of secondary hyperparathyroidism and hip bone loss in our population, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
27
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 45 publications
11
27
1
3
Order By: Relevance
“…High prevalence of vitamin D deficiency in alcohol-abusing populations were well documented by previous studies [38,39], while some researchers argued that moderate alcohol consumption showed a positive association with plasma levels of 25(OH)D [40,41]. In line with the findings by Olmos and et al [29], it was shown in our study that alcohol drinking was an independent factor inversely associated with the serum concentrations of 25(OH)D (β=-3.126, P=0.031). Neupane and et al found that shorter time since last alcohol intake was related to having lower 25(OH)D levels [38].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…High prevalence of vitamin D deficiency in alcohol-abusing populations were well documented by previous studies [38,39], while some researchers argued that moderate alcohol consumption showed a positive association with plasma levels of 25(OH)D [40,41]. In line with the findings by Olmos and et al [29], it was shown in our study that alcohol drinking was an independent factor inversely associated with the serum concentrations of 25(OH)D (β=-3.126, P=0.031). Neupane and et al found that shorter time since last alcohol intake was related to having lower 25(OH)D levels [38].…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, an inverse association between serum 25(OH)D and PTH has been well established [28]. In accordance with the results by Olmos and coworkers [29], we found that serum PTH was an independent factor (β=-0.072, P=0.002) negatively associated with the serum levels of 25(OH)D. As expected, we also demonstrated that serum calcium was an independent factor positively associated with the serum concentrations of 25(OH)D (β=17.429, P<0.0001) in the study. Consequently, to keep adequate serum calcium levels may be an approach to sufficient serum 25(OH)D, by means of increasing the intake of dietary calcium or taking calcium supplements [30].…”
Section: Discussionsupporting
confidence: 74%
“…Finally we compared our data on calcidiol plasma levels with those of a healthy cohort with 657 men and 1,154 women recently published in Spain by Olmos et al [21].…”
Section: Resultsmentioning
confidence: 99%
“…G3a (Mildly to moderately decreased, 45-59), G3b (Moderately to severely decreased, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], G4 (Severely decreased [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and G5 (Kidney failure <15). CKD is defined as either an eGFR <60 ml/min/1.73 m 2 or evidence of kidney injury such as a urinary albumin/creatinine ratio (UACR) >30 mg/g [1].…”
Section: The Kdigo 2012 Clinical Practice Guidelines For the Evaluatimentioning
confidence: 99%
“…Sin embargo, los porcentajes de riesgo de ingestas marginales de calcio, al comparar con las EAR, es del 41% de las mujeres menopáusicas. Otros estudios muestran ingestas de Ca que oscilan entre 626 y 644 mg/día en mujeres posmenopáusicas y hombres mayores de 50 años, o el estudio INDICAP en población adulta española, que observa ingestas de 991 mg/día (14)(15)(16)(17).…”
Section: Ingestas De Calcio En Españaunclassified